Cobalt chloride administration in athletes: a new perspective in blood doping? - Lippi, G.; Franchini, M.; Guidi, G. C. (British Journal of Sports Medicine, 2005)
Blood doping is an illegal and unfair way of enhancing athletic performance by increasing the oxygen carrying capacity of the blood. Currently used methods usually involve stimulation of erythropoiesis. Gene therapy targeting the hypoxia inducible factor pathway may be an attractive alternative to traditional blood doping techniques. Hypoxia activates a large number of genes with essential roles in cell and tissue adaptation to low oxygen. Cobalt chloride is a well established chemical inducer of hypoxia-like responses such as erythropoiesis. Cobalt supplementation is not banned and therefore would not be detected by current anti-doping testing. Although there is as yet no direct or anecdotal evidence of cobalt chloride administration to athletes, its use should be warned against as being not only unfair but potentially dangerous.